Pembiayaan Mudharabah dan Musyarakah Terhadap Profitabilitas pada Bank Umum Syariah di Indonesia - Laila Rokhmah; Euis Komariah (MBIA, 2017)
This study was aimed to determine how much influence of mudharabah financing and musyarakah financing to profitability by using ratio return on assets (ROA). The method was descriptive quantitative research. The samples used were 4 Islamic Banking for 5 years reserach period and 20 financial statements data. Sample were taken by using purposive sampling technique. The method used for data collection was using an external secondary data and literature in the form of annual financial statements. The analysis used multiple linear regression. The results showed that mudharabah and musyarakat financing have a significant effect simultaneously on the profitability. The partial test results showed that mudharabah financing has a significant effect on the profitability while musyarakah financing has no significant effect on the profitability